الاستراتيجية الأمريكية وتحولات النظام الدولي (Comprehensive Journal of Science, 2025)
American strategies are the means by which the United States pursues its national objectives both domestically and internationally, making them a central topic in international politics. These strategies focus on several goals, such as enhancing economic and technological power, improving national security, and influencing political changes worldwide. This study focuses on identifying the most important tools and elements of American strategies that have enabled it to maintain its dominance in the global system amidst the transformations and changes that have occurred in the international community.
Keywords: Strategy – American Strategy – American Foreign Policy – International System